Fluorine-doped porous carbon-decorated Fe3O4-FeF2 composite versus LiNi0.5Mn1.5O4 towards a full battery with robust capability. (1st July 2015) - Ming, Hai; Ming, Jun; Kwak, Won-Jin; Yang, Wenjing; Zhou, Qun; Zheng, Junwei; Sun, Yang-Kook
Graphical abstract: A new anode of fluorine doped porous Fe3 O4 -FeF2 @CFx composite with double layers of FeF2 and CFx was presented for the first time, and a high rate capability was obtained in lithium ion battery. Besides, a new full battery of Fe3 O4 -FeF2 @CFx /LiNi0.5 Mn1.5 O4 with a high capacity of 565 mAh g −1 ( vs . anode) at the current density of 100 mA g −1 was successfully introduced. It demonstrated a robust rate capability, high operating potential of 3.3 V and fine cycle ability over 50 cycles with capacity retention of 81.5%. Highlights: A new anode of fluorine-doped porous Fe3 O4 -FeF2 @CFx composite is readily prepared. The CFx layer enhances the conductivity of Fe3 O4 and ensures a fast Li + diffusion. The FeF2 can stabilize the structure of Fe3 O4 during the (dis) charge process. The Fe3 O4 -FeF2 @CFx can deliver a high capacity with a robust rate capability. A full cell of Fe3 O4 -FeF2 @CFx /LiNi0.5 Mn1.5 O4 with high performance is assembled. Abstract: A new fluorine-doped porous carbon-decorated Fe3 O4 -FeF2 composite, referred to as Fe3 O4 -FeF2 @CFx, was prepared for the first time. The formation mechanism is discussed, and a new concept of introducing double layers of FeF2 and CFx into the oxide-based anode is presented for lithium ion batteries. Varying the amount of fluorine precursor, derivatives of Fe3 O4 @CFx and FeF2 @CFx were further obtained, allowing an original analysis of their electrochemical behaviors. As-prepared Fe3 O4 -FeF2 @CFx can deliver a high capacity of 718 mAh g −1 at 50 mA g −1 . Under a hash rate of 1600 mAg −1, the capacity of Fe3 O4 -FeF2 @CFx (around 338 mAh g −1 ) is higher than that (200 mAh g −1 ) of FeF2 @CFx . Further, its capacity retention of 97% over 100 cycles is much better than the 59.4% observed for Fe3 O4 @CFx . The positive effect of the CFx layer on the electronic conductivity and ionic diffusion ability was confirmed. The role of FeF2 in the stabilization of the structure of CFx and Fe3 O4 is also discussed. Further, a new battery composed of Fe3 O4 -FeF2 @CFx /LiNi0.5 Mn1.5 O4 with a robust rate capability was assembled and delivered a reversible capacity of 565 mAh g −1 ( vs. anode) at 100 mA g −1 with a high potential of 3.3 V and a capacity retention of 81.5% over 50 cycles.